2021
DOI: 10.1177/21650799211016903
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Violence Prevention: Flagging Practices and Challenges in Hospitals

Abstract: Background: Flagging is a standardized way to communicate the risk of patient violence to workers. We add to the limited body of research on flagging by describing hospitals’ approaches to and challenges with flagging patients with a history of violent behavior. Methods: We used a qualitative case study approach of hospitals in Ontario, Canada and their patient flagging practices. Key informants and our advisory committee identified 11 hospitals to invite to participate. Hospitals assisted in recruiting frontl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Risk assessment advocates claim that risk assessments can be employed by hospitals to safeguard physicians and to reduce the incidence of violence [ 19 , 35 , 37 ]. However, its opponents are concerned that applying policies and procedures that flag individuals would lead to patient stigmatization and damage patient privacy [ 38 , 39 ]. Although implementation of patient risk assessments is controversial, some countries have adopted practical measures to flag patient based on risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Risk assessment advocates claim that risk assessments can be employed by hospitals to safeguard physicians and to reduce the incidence of violence [ 19 , 35 , 37 ]. However, its opponents are concerned that applying policies and procedures that flag individuals would lead to patient stigmatization and damage patient privacy [ 38 , 39 ]. Although implementation of patient risk assessments is controversial, some countries have adopted practical measures to flag patient based on risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…These include screening and flagging potentially violent patients, activating behavior response teams, staff education and training, and postassault debriefing. [14][15][16] A Cochrane review of staff education and training studies showed no significant direct effects on the incidence of patient violence, although educational programs may have improved knowledge and attitudes among healthcare workers. 17 Another Cochrane review that included interventional studies from 2 psychiatric units and an emergency department showed that regular violence-risk assessments reduced aggression against healthcare workers.…”
Section: Violent Event Severity Tool For Reporting Violent Incidentsmentioning
confidence: 99%
“…Various strategies have been recommended to prevent and manage violent behaviors. These include screening and flagging potentially violent patients, activating behavior response teams, staff education and training, and postassault debriefing 14-16 . A Cochrane review of staff education and training studies showed no significant direct effects on the incidence of patient violence, although educational programs may have improved knowledge and attitudes among healthcare workers 17 .…”
mentioning
confidence: 99%
“…Researchers are also being asked to develop visuals of their work - like co-author E.M.F. who was invited by a journal to create a visual abstract of her research for promotion on the journal’s social media platforms (Ferron et al, 2021).…”
Section: Introductionmentioning
confidence: 99%